Hyperreactive B cells instruct their elimination by T cells to curb autoinflammation and lymphomagenesis. - Diehl, Carina; Soberón, Valeria; Baygün, Seren; Chu, Yuanyuan; Mandelbaum, Jonathan; Kraus, Laura; Engleitner, Thomas; Rudelius, Martina; Fangazio, Marco; Daniel, Christoph; Bortoluzzi, Sabrina; Helmrath, Sabine; et al. (Immunity, 2025)
B cell immunity carries the inherent risk of deviating into autoimmunity and malignancy, which are both strongly associated with genetic variants or alterations that increase immune signaling. Here, we investigated the interplay of autoimmunity and lymphoma risk factors centered around the archetypal negative immune regulator TNFAIP3/A20 in mice. Counterintuitively, B cells with moderately elevated sensitivity to stimulation caused fatal autoimmune pathology, while those with high sensitivity did not. We resolved this apparent paradox by identifying a rheostat-like cytotoxic T cell checkpoint. Cytotoxicity was instructed by and directed against B cells with high intrinsic hyperresponsiveness, while less reactive cells were spared. Removing T cell control restored a linear relationship between intrinsic B cell reactivity and lethal lymphoproliferation, lymphomagenesis, and autoinflammation. We thus identify powerful T cell-mediated negative feedback control of inherited and acquired B cell pathogenicity and define a permissive window for autoimmunity to emerge.
EVALuna2:578193